2011
DOI: 10.1007/s12298-011-0089-z
|View full text |Cite
|
Sign up to set email alerts
|

An efficient plant regeneration system through callus for Pseudarthria viscida (L.) Wright and Arn., a rare ethnomedicinal herb

Abstract: The purpose of this study was to develop a protocol to induce high frequency of callus and subsequent plantlet regeneration for Pseudarthria viscida; an important medicinal plant. The cotyledonary node and young leaf pieces (1× 0.5 cm, length × breadth) were used as explants for callus induction and subsequent shoot regeneration and adventitious roots induction from the shoots. The best results were achieved on the following media: (1) 96 % callus induction from cotyledonary node explants on MS medium suppleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
(19 reference statements)
1
3
0
Order By: Relevance
“…Sulaiman and Toma [ 25 ] achieved successful callus induction in Arbutus andrachne using nodal explants. Similar results have also been documented in other plants, including Pseudarthria viscida [ 26 ] and Lycopersicon esculentum [ 27 ]. Plant nodes contain meristematic tissues that are easy to reactivate, with high concentrations of plant hormones (cytokinins and auxins) in the plant body providing high callus productivity [ 28 ].…”
Section: Discussionsupporting
confidence: 88%
“…Sulaiman and Toma [ 25 ] achieved successful callus induction in Arbutus andrachne using nodal explants. Similar results have also been documented in other plants, including Pseudarthria viscida [ 26 ] and Lycopersicon esculentum [ 27 ]. Plant nodes contain meristematic tissues that are easy to reactivate, with high concentrations of plant hormones (cytokinins and auxins) in the plant body providing high callus productivity [ 28 ].…”
Section: Discussionsupporting
confidence: 88%
“…In Dorema ammoniacum, various explants such as root, hypocotyls and cotyledon segments were used for callus induction and the best response was observed from root segments (Irvani et al 2010). Similarly, in Pseudarthria viscid also callus formation was affected by the source of the explants and cotyledonary node was most responsive for callus induction followed by leaf explants (Cheruvathur and Thomas 2011). In this study, 2, 4-D was found to be essential for callus induction as well as multiplication.…”
Section: Discussionmentioning
confidence: 59%
“…In vitro propagation has been successfully applied for the conservation of a large number of endangered plant species that have limited reproductive capacity and exist in threatened habitats (Fay 1992;George et al 2008;Pence 2010). Recently, there have been a number of established protocols for in vitro propagation of rare and threatened medicinal plants such as Dysosma versipellis (Jiang et al 2012), Polygonatum verticillatum (Bisht et al 2012), Pseudarthria viscida (Cheruvathur and Thomas 2011), and Thymus lotocephalus (Coelho et al 2012).…”
Section: Introductionmentioning
confidence: 99%